Improving Writing Culture through the “Simak Baca Pagi” Program in Students: Elementary School Literacy - Ilmi Nurizqi Aslama; Fatmawati Nur Hasanah (Madako Elementary School, 2024)
The "Simak Baca Pagi" Program is a literacy program that aims to increase students' interest in reading and writing. The purpose of this study is to evaluate the impact of the program on the growth of the reading and writing culture of students in grade V of elementary school. Field research, or field research, is conducted using a descriptive qualitative approach. The data used in this study include primary data from interviews with teachers, principals, and students, as well as secondary data from references such as books, journals, and related scientific articles. The data collection techniques used include documentation, observation, and in-depth interviews. Data reduction, data presentation, and conclusion drawing are the three main stages in the data analysis process. The results showed that the program, which involved habituating literacy every morning, providing a reading corner, and visiting the library, proved to be effective in increasing students' interest in reading, writing skills, and their critical thinking skills. The conclusion of this study is that literacy programs like this can be used as a model for the habituation of reading and writing activities that reflect a good literacy culture.